1986
DOI: 10.1139/m86-046
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of syringacin W-1, a bacteriocin produced by Pseudomonas syringae pv. syringae

Abstract: Syringacin W-1, a bacteriocin produced by Pseudomonas syringae pathovar syringae strain PsW-1, is a 20 × 75 nm rod-shaped particle composed of an inner core and outer sheath. Production of syringacin W-1 in broth was induced with 0.1 μLg/mL mitomycin C. The bacteriocin was purified from culture lysates using ultrafiltration, rate zonal centrifugation in sucrose gradients, and DEAE-cellulose chromatography. Purity was evaluated by subjecting syringacin W-1 preparations to electrophoresis in polyacrylamide gels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Weil-diffusion assays conducted in the presence of iron-supplemented media showed inhibitory activity similar to that determined without integration (data not shown), excluding the role of siderophores in the antimicrobial activity of Pfluorescens ATCC 948. An antagonism linked to bacterial viruses contained in the extracellular culture filtrate has been shown in pseudomonads (Vidaver, 1983;Smidt and Vidaver, 1986) and other microbial species (De Klerk and Coetzee 1961;Betz and Anderson, 1964;Hamada and Ooshima, 1975). Dilutions of the antimicrobial preparation from P fluorescens ATCC 948 produced smaller zones of inhibition and did not increase plaque formation (data not shown), thus also excluding the presence of viruses in the culture supernatant.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Weil-diffusion assays conducted in the presence of iron-supplemented media showed inhibitory activity similar to that determined without integration (data not shown), excluding the role of siderophores in the antimicrobial activity of Pfluorescens ATCC 948. An antagonism linked to bacterial viruses contained in the extracellular culture filtrate has been shown in pseudomonads (Vidaver, 1983;Smidt and Vidaver, 1986) and other microbial species (De Klerk and Coetzee 1961;Betz and Anderson, 1964;Hamada and Ooshima, 1975). Dilutions of the antimicrobial preparation from P fluorescens ATCC 948 produced smaller zones of inhibition and did not increase plaque formation (data not shown), thus also excluding the presence of viruses in the culture supernatant.…”
Section: Discussionmentioning
confidence: 71%
“…The proteinaceous nature of the antimicrobial compound purified in this study, together with the high molecular mass and the absence of carbohydrate and lipid moities (treatments with acetone and nbutanol did not modify the inhibitory activity of P fluorescens ATCC 948 supematant) (Iacobellis et al, 1992) seem to exclude the compound from this category. Bacteriocins with features quite similar to those determined for the antimicrobial compound produced by P fluorescens ATCC 948 (active protein moiety, molecular mass of -60 kDa, optimal production at 20 "C and a certain degree ofthermostability) have been shown in P syringae pv syringae (Smidt and Vidaver, 1986), P syringae susbp savastanoi (lacobellis et al, 1995), P solanacearum (Cuppels et al, 1978), P phaseolicola and P glycinea (Vidaver et al, 1972). By comparing these studies, the main difference lies in a narrower spectrum of activity, in sorne cases species-specific, which characterizes the isolated bacteriocins.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Syringacins 4-A and W-1 are high-molecular-weight and heatsensitive bacteriocins identified and purified from two strains of Pseudomonas syringae pv. syringae isolated from corn and beans, respectively (5,17). Applicative studies on disease control using bacteriocin-producing bacteria have also been reported (1,13).…”
mentioning
confidence: 99%
“…glycines was first reported by Fett et al (5), who chose the term glycinecin to differentiate the X. campestris bacteriocin from the glycin produced by P. syringae pv. glycinea (21). Previously, X. campestris pv.…”
mentioning
confidence: 99%